Stress and coping techniques of overseas Filipino workers of Poblacion, Miag-ao. - Taleon, Krizna Jan A
This study aimed to identify the sources of stress faced by the Overseas Filipino Workers (OFWs) of Poblacion Miagao, and their coping techniques and the sources of social support used by the OFWs of Poblacion, Miagao., Thirty-three (33) OFWs of Poblacion Miagao were randomly chosen as respondents for the study. Data was gathered using a questionnaire which is composed of 4 parts namely Sources of stress which was patterned after the study of Samonte (1996). COPE Inventory (Carver, Scheir and Weintraub, 1989); Sources of Social support; and the Background Information on the responents. Respondents identified working conditions specifically being overworked is the most common stressor faced by the OFWs of Poblacion, Miagao. The coping techniques that were most frequently used by the OFWs to deal with stressors were religious coping technique which has a mean score of 10.42 and positive reinterpretation and growth with a mean score of 9.15. Positive reinterpretation includes items like: "I try to grow as a person as a result of the experience and I try to see things in a different light, to make it seem more positive". Positive reinterpretation is similar to positive reappraisal which is a cognitive process through which people focus on the good on what has happened (Folkman, 1997). Most of the respondents turned to their fellow Filipinos who were working abroad and to church organizations to seek social support. Non-government agencies (NGOs) were least considered as a source of social support.